Regulatory effects of CaCl2, sodium isoascorbate, and 1‐methylcyclopropene on chilling injury of banana fruit at two ripening stages and the mechanisms involved. Issue 2 (18th August 2017) - Jiao, Wenxiao; Xi, Yu; Cao, Jiankang; Fan, Xinguang; Jiang, Weibo
Abstract: To improve fruit chilling tolerance during postharvest storage, banana fruit at two ripening stages (green and yellow) were pretreated with 2% (wt/vol) CaCl2 (Ca 2+ ) or 1% (wt/vol) sodium isoascorbate (SI) under vacuum infiltration, or fumigated with 1.0 μL/L 1‐methylcyclopropene (1‐MCP), then stored at 6 °C. Application of Ca 2+ or SI significantly reduced chilling injury index, electrolyte leakage, malondialdehyde content, and polyphenol oxidase activity of banana peel during storage at 6 °C. And Ca 2+ or SI also sustained levels of firmness, peel lightness, and promoted activities of peroxidase, superoxide dismutase, catalase, and ascorbate peroxidase in banana at two ripening stages. Application of 1‐MCP resulted in positive effects only on the visual quality of yellow ripening banana. Our results indicated that Ca 2+ or SI could ameliorate chilling injury of both mature green and yellow ripening banana fruit stored at 6 °C; 1‐MCP could enhance chilling tolerance of yellow ripening banana. Practical applications: Refrigeration is a usual method for extending storage life of banana fruit. Like other tropical and subtropical fruits, banana is highly susceptible to chilling injury (CI) and develops CI symptoms of rapid peel browning, pulp rigidity, and pitting when stored at low temperature. Our results indicate that 2% (wt/vol) calcium chloride or 1% (wt/vol) sodium isoascorbate are effective methods in alleviating CI of the banana at two ripening stages. A total of 1.0 μL/L 1‐methylcyclopropene significantly reduced CI of yellow ripening banana, while exacerbation of CI was observed in green maturity banana during the storage. This research not only provides environmentally friendly chemicals for postharvest application but also investigates the effects of chemical treatments on CI both of mature green banana and yellow ripening banana.